SIRT7 has a critical role in bone formation by regulating lysine acylation of SP7/Osterix - Masatoshi Fukuda (Nature Portfolio, 2018)
SP7/Osterix is a transcription factor involved in osteoblast differentiation. Here, the authors show that Sirtuin 7 activates Osterix posttranslationally by regulating its lysine acylation, and that mice lacking Sirtuin 7 in osteoblasts show reduced bone formation.